Use of echocardiographic subxiphoid five-sixth area length (bullet) method in evaluation of adequacy of borderline left ventricle in hypoplastic left heart complex - Justin T Tretter; Sujata Chakravarti; Puneet Bhatla (Wolters Kluwer Medknow Publications, 2015)
Indexed left ventricular end-diastolic volume (ILVEDV) is commonly used in evaluating "borderline left ventricle (LV)" in hypoplastic left heart complex (HLHC) to determine if the LV can sustain adequate systemic cardiac output. Commonly used quantification methods include biplane Simpson or the traditional five-sixth area length "bullet" methods, which have been shown to underestimate true LV volumes, when septal position is mildly abnormal. Subxiphoid five-sixth area length method is proposed as a more accurate estimate of true LV volume in the evaluation of borderline LV.